Ambisyllabic characteristics of Spanish resyllabification: Beyond durational cues - José María Lahoz-Bengoechea; Miguel Jiménez-Bravo (Estudios de Fonética Experimental)
In Spanish coda segments are resyllabified as the onset of a following onsetless syllable across a word boundary. Thus, buscabas ocio (‘you were looking for entertainment’) has been traditionally syllabified in the same way as buscaba socio (‘s/he was looking for an associate’), and both are considered homophones. In this study nineteen speakers were recorded producing sentences that included such two-word minimal pairs, making up a total of 1424 utterances. The acoustic analyses performed on both prosodic structures, i.e. /V#CV/ vs. /V#CV/, provide measures of amplitude, spectral characteristics, and coarticulation for /s/, /n/, and /l/, as well as for their flanking vowels. Our results show differences for each condition and suggest an ambisyllabic nature of resyllabified consonants, which is interpreted within the framework of Articulatory Phonology.